2013
DOI: 10.1007/s00535-013-0857-3
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal complications associated with gemcitabine-concurrent proton radiotherapy for inoperable pancreatic cancer

Abstract: Approximately half of the patients treated with GPT for inoperable pancreatic cancer exhibited radiation-induced ulcers in the stomach and duodenum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…In contrast to the current series demonstrating negligible toxicity for patients with locally advanced pancreas cancer treated with protons, Takatori et al [17] reported an analysis of the upper gastrointestinal complications associated with gemcitabine concurrent proton radiation therapy for patients with inoperable pancreatic cancer. The study demonstrated a 49.4% rate of gastric/duodenal ulceration in the treated patients.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast to the current series demonstrating negligible toxicity for patients with locally advanced pancreas cancer treated with protons, Takatori et al [17] reported an analysis of the upper gastrointestinal complications associated with gemcitabine concurrent proton radiation therapy for patients with inoperable pancreatic cancer. The study demonstrated a 49.4% rate of gastric/duodenal ulceration in the treated patients.…”
Section: Discussionmentioning
confidence: 71%
“…First attempts at dose escalation performed by Terashima, et al [52] and Takatori, et al [53] observed a particularly high incidence (50%) of GI radiation-induced ulcers of 50 and 126 enrolled patients, respectively. The two studies from Hyogo Ion Beam Medical Center employed a significantly a higher prescription of 2.5 to 2.7 GyE per fraction compared to other PT studies in Table 3.…”
Section: Summary Of Pt Clinical Studies Inmentioning
confidence: 99%
“…Most of the patients received a dose of 67.5 Gy (RBE) in 25 fractions. The initial report suggested tolerability of this regimen [15] ; however, a subsequent publication in the gastroenterology literature reported a high rate of upper gastrointestinal complications [16] . Post-treatment endoscopic examinations in 45 of 91 patients revealed radiation-induced ulcers in the stomach and duodenum.…”
Section: Clinical Studiesmentioning
confidence: 99%